Molecular imaging in cardiovascular diseases - Botnar, R. M.; Ebersberger, H.; Noerenberg, D.; Jansen, C. H. P.; Wiethoff, A. J.; Schuster, A.; Kasner, M.; Walter, T. C.; Knobloch, G.; Hoppe, P.; Diederichs, G.; Hamm, B.; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Cardiovascular diseases remain the leading cause of morbidity and mortality in industrialized and developing countries. In clinical practice, the in-vivo identification of atherosclerotic lesions, which can lead to complications such as heart attack or stroke, remains difficult. Imaging techniques provide the reference standard for the detection of clinically significant atherosclerotic changes in the coronary and carotid arteries. The assessment of the luminal narrowing is feasible, while the differentiation of stable and potentially unstable or vulnerable atherosclerotic plaques is currently not possible using non-invasive imaging. With high spatial resolution and high soft tissue contrast, magnetic resonance imaging (MRI) is a suitable method for the evaluation of the thin arterial wall. In clinical practice, native MRI of the vessel wall already allows the differentiation and characterization of components of atherosclerotic plaques in the carotid arteries and the aorta. Additional diagnostic information can be gained by the use of non-specific MRI contrast agents. With the development of targeted molecular probes, that highlight specific molecules or cells, pathological processes can be visualized at a molecular level with high spatial resolution. In this review article, the development of pathophysiological changes leading to the development of the arterial wall are introduced and discussed. Additionally, principles of contrast enhanced imaging with non-specific contrast agents and molecular probes will be discussed and latest developments in the field of molecular imaging of the vascular wall will be introduced.
CRIS-Team Scopus Importer:2023-03-08
Keywords: arteriosclerosis; gadolinium; MR-imaging